Mass spectrometry imaging of fingerprint sweat on nanostructured silicon. Issue 28 (18th December 2014) - Guinan, T.; Della Vedova, C.; Kobus, H.; Voelcker, N. H.
Abstract : Desorption ionisation on porous silicon mass spectrometry imaging (DIOS-MSI) was used on fingerprints to map the distribution of exogenous and endogenous molecules present in sweat. Abstract : Desorption ionisation on porous silicon mass spectrometry imaging (DIOS-MSI) was used on fingerprints to map the distribution of exogenous and endogenous molecules present in sweat. Our attention was focused on the proof-of-principle to detect illicit drugs and their metabolites to exemplify the technique's potential in the area of forensic and workplace testing.